QCD sum rules for the Delta isobar in neutron matter - Marques L, Jesuel [UNESP]; Lee, Su Houng; Park, Aaron; Matheus, R. D. [UNESP]; Jeong, Kie Sang (Amer Physical Soc, 2018)
We study the properties of the Delta isobar in the symmetric and asymmetric nuclear matter using the QCD sum rules approach based on the energy dispersion relation. Allowing for different continuum thresholds for the polarization tensors with different dimensions, we find stable masses for the Delta in both the vacuum and the medium. Compared to the nucleon case, we find that the vector repulsion is smaller for the Delta while the scalar attraction is similar (75 MeV vector repulsion and 200 MeV scalar attraction in the symmetric matter). The smaller vector repulsion can be understood using the Pauli principle and a constituent quark model. Also, the isospin dependence of the quasiparticle energy, which mainly comes from the vector self-energy, is quite weak. We also allow for an explicit pi - N continuum contribution to the polarization function but find its effect to be minimal Phenomenological consequences of our results are discussed.